2004
DOI: 10.1902/jop.2004.75.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Root Coverage Using the Coronally Positioned Flap With or Without a Subepithelial Connective Tissue Graft

Abstract: The results indicate that both surgical approaches are effective in addressing root coverage. However, when an increase in gingival dimensions (keratinized tissue width, gingival/mucosal thickness) is a desired outcome, then the combined technique (CPF + SCTG) should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
174
6
15

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(225 citation statements)
references
References 21 publications
30
174
6
15
Order By: Relevance
“…[16][17][18][19] In this study, the proportions of STTh loss in groups I and II were 64.7% and 58.8% respectively, in accordance with the results observed with CTG use. 15,16,18,20 Over an observation period of 6 months, mCM use thus seems to yield results equivalent to CTG use.…”
Section: Discussionsupporting
confidence: 90%
“…[16][17][18][19] In this study, the proportions of STTh loss in groups I and II were 64.7% and 58.8% respectively, in accordance with the results observed with CTG use. 15,16,18,20 Over an observation period of 6 months, mCM use thus seems to yield results equivalent to CTG use.…”
Section: Discussionsupporting
confidence: 90%
“…In the present systematic review there were no difference in GR reduction between the connective tissue graft and the coronally advanced flap which may raise concern over the conclusion that the former is indeed the gold standard. Despite this fact it should be noted that only two studies were available for analysis 5,49 as well as the overall comparisons (i.e., mean root coverage, complete root coverage and gain in the width of keratinized tissue) achieved by this and previous reviews 18,19 indicated better results for SCTG.…”
Section: Discussionmentioning
confidence: 83%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34] Three RCTs reported the results from samples containing less than 10 patients per group at final examination, 13,35,36 two studies were classified as randomized non-controlled trials, 37,38 two presented a follow-up period <6 months, 39,40 two did not present a patientbased analysis 41,42 and one included recession areas containing teeth with restorations. 43 Of the 23 included studies, 5,12,15,44-63 fifteen had a splitmouth group study design 5,15,[44][45][46][40][41][42][43][44][45][46][47][48][49][50][51][52][53]57,58,[60][61][62]63 and seventeen were conducted at university dental clinics 5,12,44,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Also, a randomized case-control study aimed to find out whether the tested surgical approach makes the treated sites less susceptible to future recession, should evaluate the changes in keratinized tissue dimensions in milimeters. 18,19 As MAGR include ≥2 teeth, width of each GR should be considered in such studies to verdict on the predictability of the tested technique in various clinical conditions. Additionally, survey on cosmetic evaluation of the treatment outcome should be carried out with an approved system such as 'root coverage aesthetic score (RES)', especially in studies with a follow-up period ≥1 year.…”
Section: Discussionmentioning
confidence: 99%